2008
DOI: 10.1007/s10350-007-9094-2
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Pathology and Long-Term Survival in Emergency Colorectal Cancer

Abstract: Advanced tumor pathology is a basis for poor long-term survival in emergency colorectal cancers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
78
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(93 citation statements)
references
References 11 publications
9
78
2
Order By: Relevance
“…A second issue that makes the findings of previous work hard to interpret specifically for colon cancer is the lack of differentiation that all but 2 14,15 of the discussed articles make between colon and rectal disease -an issue shared with many publications on the matter. [19][20][21] Malignancies of the colon and rectum have been shown to be quite different in tumor biology 22 and subsequent prognosis 23 and arguments to split both are a recurring issue in outcome studies. 24 Our work is therefore the first to review a large cohort of colon cancer-specific patients in a single center.…”
Section: Commentsmentioning
confidence: 99%
“…A second issue that makes the findings of previous work hard to interpret specifically for colon cancer is the lack of differentiation that all but 2 14,15 of the discussed articles make between colon and rectal disease -an issue shared with many publications on the matter. [19][20][21] Malignancies of the colon and rectum have been shown to be quite different in tumor biology 22 and subsequent prognosis 23 and arguments to split both are a recurring issue in outcome studies. 24 Our work is therefore the first to review a large cohort of colon cancer-specific patients in a single center.…”
Section: Commentsmentioning
confidence: 99%
“…Also emergency admission are increases due to patient or health system related delay (9). Emergency surgery patients mostly have more complicated and advanced disease so higher complication rates, and longer hospital stay is seen in this group (10,11,12,13,14). In our study, emergency CRC surgery patients had longer operation time, higher blood loss; higher complication rates and longer average hospital stay than elective CRC surgery patients.…”
Section: Discussionmentioning
confidence: 53%
“…All patients who presented as an emergency had intestinal obstruction. Other larger studies have reported intestinal obstruction as the commonest (78 %) mode of emergency presentation [14,15]. Bleeding per rectum was the commonest symptom (42.8 %), which was followed by change of bowel habits (17.1 %) in those who presented to the out-patient clinic.…”
Section: Clinico-pathological Parametersmentioning
confidence: 93%